Diapir Melting of Subducted Mélange Generating Alkaline Arc Magmatism and Its Implications for Material Recycling at Subduction Zone Settings. Issue 10 (20th May 2022) - Wang, Kai; Cai, Keda; Sun, Min; Wang, Xiangsong; Xia, Xiao‐Ping; Zhang, Bo; Wan, Bo
Abstract: Alkaline rocks crop out in subduction‐related volcanic arcs globally, whose genesis is explained by partial melting of hybrid diapiric mélanges in the mantle wedge. Such a new model has not yet been evidenced by field‐based investigations, where mélanges and alkaline arc rocks have spatial‐temporal and genetic connections. In this study, we identified these two types of rock units exposed in Western Tianshan, and established their petrogenetic relationship through field, geochronologic, geochemical, and thermodynamic investigations. Our results suggest that partial melts produced by melting of the mélange matrix at pressures of 2.8–2.4 GPa and 1.8–1.4 GPa with temperatures of 1000–1200°C can replicate the major‐element contents and trace‐element abundances of the regional alkaline arc rocks. This finding not only supports the hypothesis that diapir melting of subducted mélanges has a capacity to generate alkaline arc magma, but also provides insight into material recycling at subduction zone settings. Plain Language Summary: Oceanic lithosphere subduction in convergent margins is key for transferring materials from the surface to Earth's interior. The mélanges and arc rocks preserved in ancient orogenic belts may have archives to understand both processes and components of subducted materials, which is critical for our knowledge of arc magmatism and continent formation. In this study, we report these rocks in Western Tianshan, where subducted mélanges and alkaline arc rocks are spatially and temporally correlated. Upon field, geochronologic, geochemical, and thermodynamic investigation, we propose that at the late stage of oceanic lithosphere subduction, high‐pressure mélange rocks, on the one hand, were rapidly exhumed from depths along the cold subduction channel and, on the other hand, their melted equivalents may migrate buoyantly into the hot mantle wedge to have generated alkaline magmas. Our study establishes the genetic connections between high‐pressure mélanges and alkaline arc rocks, and provides new insight into material recycling at subduction zone settings. Key Points: Late Carboniferous alkaline arc rocks and high‐pressure mélanges exposed in Western Tianshan are closely correlated in genesis Mélange diapir melting is a plausible mechanism to generate alkaline arc magmas Both physical exhumation and diapir melting may be two possible pathways for mélange transfer at subduction settings